Speech of Alaverdi-Khan Undiladze at the Court of Shah Abbas I - Elguja Khintibidze (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2012)
In the present edition of "The Kartvelologist" Alaverdi-Khan Undiladze's speech at the royal court of Shah-Abbas I, proposing the resumption of the Persian-Turkish war delivered by him at the end of 16th century is published. This important historical source comes for the first time in the area of research of Georgian orientalists. It is preserved in the book of the English diplomat Antony Sherley on his travel to Persia (Sir Antony Sherley, His Relation of His Travels into Persia, London 1613). The Georgian translation is being published along with the original.